Multimedia for Culinary Students: Food and Beverage Processing Subject - Cok. Istri Raka Marsiti; I Wayan Santyasa; Sudatha, Gde Wawan; Sudarma, I Komang (Universitas Pendidikan Ganesha, 2022)
The use of learning media is less varied, monotonous, and still one-way. This study aims to develop multimedia on food and beverage processing elements and the sub-elements of hot and cold appetizers. This type of research is development. The model used for product development is the ADDIE model. The subjects of this study consisted of 2 learning content experts, 2 learning design experts, and 2 learning media experts. The product trial subjects totaled 40 students from class XII. The instrument used in this research is a questionnaire. The data analysis technique used in this study is descriptive qualitative, quantitative, and statistical inferential analysis techniques. The results of this study are that the process of developing learning multimedia in the elements of food and beverage processing, the sub-elements of hot and cold appetizers, obtains very good qualifications from experts and students so that they are suitable for use in learning. The use of multimedia learning can help students understand the material because it is equipped with concrete examples in the form of pictures and videos and can create student interaction in the learning process because students can operate and respond to questions given in this interactive learning multimedia, not just see and hear.